2012
DOI: 10.1007/s11695-012-0671-7
|View full text |Cite
|
Sign up to set email alerts
|

Low Anastomotic Stricture Rate After Roux-en-Y Gastric Bypass Using a 21-mm Circular Stapling Device

Abstract: We hereby demonstrate that the construction of GJ anastomosis with a 21-mm circular stapler is associated with a low stricture rate using our standardized technique. Strictures are amenable to balloon dilatation with subsequent long-term resolution of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Sima et al reported a greater incidence of vomiting and need for endoscopic dilation over a 5-year follow-up period in those patients for whom the C21 technique was used for GJA [ 14 ]. However, some authors have demonstrated low rates of GJ stricture with the 21-mm staplers (0.8–5.9%) [ 16 , 17 ]. Factors associated with formation of stricture at the GJA include a 21-mm diameter CS and a 4.5-mm staple height.…”
Section: Discussionmentioning
confidence: 99%
“…Sima et al reported a greater incidence of vomiting and need for endoscopic dilation over a 5-year follow-up period in those patients for whom the C21 technique was used for GJA [ 14 ]. However, some authors have demonstrated low rates of GJ stricture with the 21-mm staplers (0.8–5.9%) [ 16 , 17 ]. Factors associated with formation of stricture at the GJA include a 21-mm diameter CS and a 4.5-mm staple height.…”
Section: Discussionmentioning
confidence: 99%
“…Others have obtained a low rate of stricture using a 21-mm inserted trans-orally, but passing the anvil into the posterior wall of the gastric pouch but noting if specifically incorporating the gastric pouch staple line. Rondan et al reported 4.7 % stricture rate in 338 cases of LRYGB which were performed using 21 mm circular staplers [5]. The authors, however, attributed this low rate partly to the tension-reducing effect of the retrogastric, retrocolic approach they used for the alimentary limb and the anterior stitches at the GJ anastomosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Rondan et al reported 4.7 % stricture rate in 338 cases of LRYGB which were performed using 21 mm circular staplers [5]. The authors, however, attributed this low rate partly to the tension-reducing effect of the retrogastric, retrocolic approach they used for the alimentary limb and the anterior stitches at the GJ anastomosis [5]. On the contrary, all cases in our series were performed with an antegastric antecolic fashion and we obtained a similar stricture rate using the 21-mm than Rondan et al and Suter et al; both of which employed retrocolic passage of the alimentary limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations